2019
DOI: 10.2298/tsci180406188k
|View full text |Cite
|
Sign up to set email alerts
|

Study of the phenomenon of the interaction between sessile drops during evaporation

Abstract: This research work represents an experimental study of the interaction between water drops deposited on a substrate at ambient temperature. To examine this phenomenon, the evaporation of a single drop deposited on a substrate was first investigated. Then, several drops were deposited alongside on the same substrate under the same conditions. The central drop dynamic behavior was also examined and compared with that of a single drop. This comparison shows the effect of the interaction between the neighboring dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…To this end, we compare the theoretical predictions of the present model with the recent experimental results of Khilifi et al (2019) for seven relatively closely spaced droplets. Khilifi et al (2019) studied the evaporation of sessile droplets of water at an initial temperature of 20 • C on a sapphire substrate into an enclosed chamber with 50 % humidity at an ambient temperature of 21 • C. Initial experiments using an isolated droplet revealed that the droplets evaporate in an SS mode with an initial contact angle ofθ 80 • and a receding contact angle of θ 36 • . To investigate the interactions between the droplets, they then studied a (slightly imperfect) 'I'-shaped configuration of seven nearly identical droplets with approximate radius 7.5 × 10 −4 m and volume 7 × 10 −10 m 3 a distance 2 × 10 −4 m apart (their 'Configuration (b)').…”
Section: Radially Integrated Evaporative Flux R Kmentioning
confidence: 84%
See 1 more Smart Citation
“…To this end, we compare the theoretical predictions of the present model with the recent experimental results of Khilifi et al (2019) for seven relatively closely spaced droplets. Khilifi et al (2019) studied the evaporation of sessile droplets of water at an initial temperature of 20 • C on a sapphire substrate into an enclosed chamber with 50 % humidity at an ambient temperature of 21 • C. Initial experiments using an isolated droplet revealed that the droplets evaporate in an SS mode with an initial contact angle ofθ 80 • and a receding contact angle of θ 36 • . To investigate the interactions between the droplets, they then studied a (slightly imperfect) 'I'-shaped configuration of seven nearly identical droplets with approximate radius 7.5 × 10 −4 m and volume 7 × 10 −10 m 3 a distance 2 × 10 −4 m apart (their 'Configuration (b)').…”
Section: Radially Integrated Evaporative Flux R Kmentioning
confidence: 84%
“…Previous studies of the evaporation of multiple sessile droplets have used a variety of experimental, numerical and analytical approaches (Lacasta et al 1998;Schäfle et al 1999;Kokalj et al 2010;Sokuler et al 2010;Carrier et al 2016;Castanet et al 2016;Shaikeea et al 2016;Shaikeea & Basu 2016a,b;Hatte et al 2019;Khilifi et al 2019;Schofield et al 2020). The critical difference in comparison with what is observed with a single droplet is the occurrence of 'shielding', in which the presence of other droplets causes a droplet to evaporate more slowly than it would in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Our reference point is the lifetime of a single droplet with initial semi-widthR 0 , which from (1), (37) and (38) is given bŷ…”
Section: Comparison Between the Lifetimes Of A Single Droplet And A Pmentioning
confidence: 99%
“…In practice, droplets rarely occur in isolation, and so it is important to understand how droplets evaporate in the presence of other evaporating droplets. Previous studies of the evaporation of multiple sessile droplets have employed a variety of experimental, numerical and analytical approaches [27][28][29][30][31][32][33][34][35][36][37][38]. The critical difference between the evaporation of single and of multiple droplets is the occurrence of the shielding effect, namely that the presence of other evaporating droplets increases the local vapour concentration, and so each droplet evaporates more slowly than it would in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the flow evaporated at the liquid-gas interface has been the subject of several works. For example, Dorra Khilifi et al [5] studied experimentally the neighborhood effect on the evaporation of a water drop. By carrying this study, they proved that the total evaporation of drops, which were close to each other, was noticeable minimized, compared to that of a single drop.…”
Section: Introductionmentioning
confidence: 99%